EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN DISCOVERY LEARNING (DL) DENGAN PENDEKATAN SAINTIFIK PADA MATERI SEGIEMPAT DITINJAU DARI KECEMASAN BELAJAR MATEMATIKA SISWA SMP NEGERI KELAS VII DI KABUPATEN BANYUMAS - Fadlilah, Umi; Usodo, Budi; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aims of the research were to determine the effect of learning models on mathematics achievement viewed from anxiety mathematics learning. The learning models compared were direct, PBL with scientific approach, and DL with scientific approach. This was quasi-experimental research with 3x3 factorial design. The population were all students of Junior High School in Banyumas. The samples are the students of SMPN 1 Patikraja, SMPN 2 Patikraja, and SMPN 2 Kalibagor, taken by using stratified cluster random sampling technique. The instruments used were mathematics achievement test and anxiety mathematics learning. The data analysis technique used unbalanced two ways anova. Based on the data analysis, it can be concluded as follows. (1) The students receiving PBL with scientific approach to DL with scientific approach achievement than those receiving direct learning model. The students receiving PBL with scientific approach and DL with scientific approach had the same learning outcome. (2) Students with lower levels of mathematics anxiety learning had better learning outcome than students with medium and high anxiety level. Studentsâ learning anxiety level on math was better in their learning outcome than students with high levels of learning anxiety mathematics. (3) In each group, the anxiety level of students learning mathematics, learning model PBL with scientific approach and learning model DL with scientific approach provides better performance than direct learning model, learning model PBL with scientific approach produces the same learning outcome with learning model DL with scientific approach. (4) In each of the learning model, students with lower levels of anxiety level of mathematics learning outcome had better math outcome than students with medium and high math anxiety level learning, students learn math anxiety levels were to have better learning outcome than students with high levels of anxiety learn mathematics.Keywords: Direct learning model, PBL learning model with scientific approach, DL learning model with scientific approach, Math Anxiety Learning